FORMULASI STRATEGI HOTEL DANAU DARIZA MENGGUNAKAN ANALISIS SWOT DAN QSPM MATRIX - Tefirmansyah, Salwa Khoirunnisa; Alamsyah, Muhammad Iqbal (eProceedings of Management, 2025)
Hotel Danau Dariza is one of the leading accommodations in Garut Regency, featuring traditional architecture inspired by local cultural heritage. However, the hotel has experienced a decline in occupancy rates due to increasing competition and shifting tourist preferences toward digitalized services. This study aims to formulate an effective business development strategy to enhance the hotel’s competitiveness. The research employs a descriptive qualitative approach using the Quantitative Strategic Planning Matrix (QSPM), which includes the input stage (IFE and EFE matrices), matching stage (SWOT and IE matrices), and decision stage (QSPM). The analysis results indicate that Hotel Danau Dariza falls into the "hold and maintain" strategic position, with an Internal Factor Evaluation (IFE) score of 2,778, and an External Factor Evaluation (EFE) score of 2,407. The prioritized strategy is product development, in the form of adding and modifying services, with the highest Total Attractiveness Score (TAS) of 6,027. This strategy is considered the most appropriate for enhancing customer experience, strengthening competitive advantage, and increasing hotel occupancy in a sustainable manner. Keywords: Matriks IFE, Matriks EFE, Matriks SWOT, Matriks IE, QSPM